Environmental Kuznets curve (EKC) : a manual - Ozcan, Burcu; Ozturk, Ilhan (Academic Press, 2019)
Environmental Kuznets Curve (EKC): A Manual provides a comprehensive summary of the EKC, summarizing work on this economic tool that can analyze environmental pollution problems. By enabling users to reconcile environmental and economic development policies, Environmental Kuznets Curve studies lend themselves to the investigation of the energy-growth and finance-energy nexus. The book obviates a dependence on outmoded tools, such as carrying capacity, externalities, ecosystem valuation and cost benefit analysis, while also encouraging flexible approaches to a variety of challenges.